DONGENG MIRNA REFLEKSI KEJAHATAN SEKSUAL DALAM MONOLOG - Nurul Huda (Institut Seni Indonesia Surakarta, 2014)
Dongeng Mirna (The story of Mirna) tells about an old man who kills his wife of her infidelity with their gardener,Sulaiman. The story that is packed in a monologue drama is inspired by the booming cases about sexualcrime that finally come to the murder. The work creator acts both as the teller as well as the main characterin the story that has love and fidelity even at the end he is dead because of drinking the poison. All of theprocess as well as the performance of Dongeng Mirna take place in Kemlayan Art Space belongs to thedance maestro, Sardono W. Kusumo.Keywords: love, devotion, sexual crime, monolog